2004
DOI: 10.1074/jbc.m403823200
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Events Involved in Macrophage Chemokine Expression in Response to Monosodium Urate Crystals

Abstract: Chemokine production has been associated with leukocyte infiltration into the joint during gouty arthritis, and monosodium urate (MSU) crystals, the causative agent of this arthropathy, have been shown to modulate their expression. In the present study, we investigated the transductional mechanisms underlying this cellular regulation in the murine macrophage cell line B10R. We report that MSU crystals rapidly and transiently increase mRNA levels of various chemokines in a concentration-dependent manner. Examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
44
2
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 51 publications
5
44
2
2
Order By: Relevance
“…MSU crystals have been shown to induce upregulation and post-translational stabilisation of CCL2 mRNA in vitro (33) whereas synoviocytes and mesothelial cells appear to possess stores of MCP-I ready for immediate release upon MSU crystal stimulation (13,16). This differential regulation of CCL2 production may be one reason why only membrane CCL2 production was observed during the first 8 hours of MSU crystal stimulation in this study.…”
Section: Resident Macrophage Depletion Abrogates Msu Crystal-induced contrasting
confidence: 42%
“…MSU crystals have been shown to induce upregulation and post-translational stabilisation of CCL2 mRNA in vitro (33) whereas synoviocytes and mesothelial cells appear to possess stores of MCP-I ready for immediate release upon MSU crystal stimulation (13,16). This differential regulation of CCL2 production may be one reason why only membrane CCL2 production was observed during the first 8 hours of MSU crystal stimulation in this study.…”
Section: Resident Macrophage Depletion Abrogates Msu Crystal-induced contrasting
confidence: 42%
“…TREM-1-mediated tyrosine phosphorylation, activation of MAPK, and mobilization of Ca 2ϩ might also lead to the activation of transcription complexes, which could have a synergistic effect with NF-B in promoting the expression of proinflammatory genes. It has also been shown that MSU crystals potentially activate the NF-B signaling pathway (23). Overall, these findings suggest that TREM-1 may act synergistically with MSU crystals in promoting the production of proinflammatory cytokines through activation of NF-B and MAPK, tyrosine phosphorylation, and mobilization of Ca 2ϩ .…”
Section: Discussionmentioning
confidence: 73%
“…TLRs are type I transmembrane receptors characterized by the presence of extracellular leucine-rich repeat motifs that recognize pathogenassociated molecular patterns (26). Most TLRs have a cytoplasmic Toll/IL-1 receptor (IL-1R) domain, which is required for the activation of downstream signaling pathways that lead to the activation of NF-B (26), a transcription factor activated rapidly by MSU crystals and centrally involved in MSU crystal-induced cell activation (27,28). In response to pathogen-associated molecular patterns, the canonical TLR signaling pathway recruits the cytosolic TLR adapter protein myeloid differentiation factor 88 (MyD88), IL-1R-activated kinase, and TNF receptor-associated factor 6 to activate IKKs, and the process culminates in NF-B-mediated expression of proinflammatory messenger RNA (26).…”
mentioning
confidence: 99%